MASTERY LEARNING: IMPLICATIONS FOR NURSING - Whittington, Callie (Acta Scientiae et Intellectus, 2024)
Mastery learning is a concept that has been around for over 40 years, but is currently making its application into both the nursing and adult learner world (Cooperman, 2011). This paper gives insight to mastery learning and its application to the adult learner, specifically in the nursing education realm. Utilizing such areas of technology as simulation, students will be able to practice their skills and feel confident in them prior to patient care. Instructors can combat the application barrier by utilizing different techniques during delivery of content. Such national problems as nursing and nursing educator shortages have proven to be a barrier to effective application of the mastery learning concept. There are advantages and disadvantages alike to this learning mastery with implementation for the student and teacher.